Analisis Faktor-Faktor Yang Mempengaruhi Pengetahuan Swamedikasi Analgetika Pada Nelayan Di Kecamatan Banyuates - Haris, M. Shofwan; Supa'i, Aisyah Fitriani (NHM PRESS, 2025)
Analgesic self-medication is an independent action in managing pain that is commonly done by fishermen due to heavy physical activity that continues. The purpose of this study to analyze the factors that affect the level of knowledge of analgesic self-medication among fishermen in Banyuates Sub-district. This study used cross-sectional and observational design and involved 97 fishermen respondents selected through purposive sampling method. A standardized questionnaire was used to colled data, wich was then analysed descriptively and using the chi-square test to identify the relationship between variables with α = 0.05. The results showed that 30% of respondents have high knowledge, 45% were moderate, and 25% were low, the highest level of knowledge was in the moderate category, namely 45%. Factors that are proven to have a significant effect on the level of knowledge are education (p = 0.000), information (p = 0.014), information sources (p = 0.009), and the environment (p = 0.002). Meanwhile, age, experience, interest, and socio-cultural factors did not show a significant relationship (p > 0.05). This study confirms the importance of increasing education and access to accurate information to improve rational self-medication knowledge among fishermen. In addition, researchs are expected to look at factors that have not been studied, such as economic influences, or the availability of health facilities.